Some nanograined ferrites and perovskites for catalytic combustion of acetone at low temperature. Issue 3 (April 2015) - Rezlescu, Nicolae; Rezlescu, Elena; Dorin Popa, Paul; Doroftei, Corneliu; Ignat, Maria
Abstract: Two types of nanograined oxide compounds, CuFe2 O4, MgFe2 O4, Ni0.5 Co0.5 Fe2 O4, with spinel-type structure, and SrMnO3, FeMnO3, La0.6 Pb0.2 Ca0.2 MnO3 with perovskite-type structure, were prepared by sol–gel self-combustion method and tested for the catalytic combustion of dilute acetone in air. Their structure and surface properties were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), BET surface area measurements and energy-dispersive X-ray spectroscopy (EDX). We chose acetone as a VOC model because, among all VOCs, it is a common organic solvent extensively used in the manufacture of plastics, fibers, drugs and other chemicals. The catalytic activity studies revealed that between these two types of catalysts, the perovskite catalysts exhibited the best activity in the catalytic combustion of acetone. The acetone conversion degree over perovskite catalysts can exceed 95% at 300 °C, while over ferrospinel catalysts it is of about 70%. Our experimental results indicate that the SrMnO3 and La0.6 Pb0.2 Ca0.2 MnO3 perovskites are the preferred catalysts in the catalytic combustion of acetone at low temperatures. The time stability of La0.6 Pb0.2 Ca0.2 MnO3 catalyst for acetone combustion was also investigated and no deactivation was observed for 36 h at 250 °C.